Muscle strength parameters of single joint or joint chain under different motion modes and angular velocities by isokinetic muscle test - Mi, S.-Q.; Qian, L. (Journal of Clinical Rehabilitative Tissue Engineering Research, 2018)
BACKGROUND: The isokinetic muscle strength test is mainly performed in adult tennis players, and the main tested parts are shoulder joint or single joint. There is a lack of large-sample report on the isokinetic muscle strength of the lower limb joints at different angular velocities in young male tennis players. OBJECTIVE: To analyze the properties of the muscle strength of lower limb joints in young tennis players, and to investigate the changes of the test data at different angular velocities. METHODS: Totally 162 young male tennis players were enrolled to perform isokinetic muscle strength test on bilateral hips, knee and ankle joints using IsoMed 2000: (60 (°)/s (absolute force), 5 times, and 240 (°)/s (explosive force), 25 times. The relative peak torque, the antagonistic/active muscle ratio, the heteronymous muscle strength ratio and the muscle endurance index of the left and right sides were analyzed using paired t test. RESULTS AND CONCLUSION: The relative peak torque of left hip flexor burst was significantly higher than that of the right hip flexor burst (P < 0.05), and the right extensor explosive force was significantly higher than that of the left side (P < 0.01). The left knee flexion, absolute force and explosive force of flexor were significantly larger than those of the right side (P < 0.05). The left ankle flexor power was significantly higher than that of the right side (P < 0.05). The ratio of peak torque of the lower limb at different angular velocities: the hip, knee and ankle joint flexor force absolute ratio was 1.6 : 1.4 : 1. The ratio of the absolute force of the extensor was 10.8 : 7.4 : 1. The flexor force of the hip, knee and ankle joints was 1.3 : 1.2 : 1. The explosive force of the extensor was 9.2 : 8.2 : 1. Antagonistic/active muscle ratio: the hip, knee and ankle joints were 0.56, 0.73, and 3.86 in the absolute force test, respectively. The hip, knee and ankle joints were 0.65, 0.60 and 4.66, respectively in the explosive force test. There were significant differences in the explosive force between left and right sides of the hip and ankle joints (P < 0.05). The heteronymous muscle strength ratio: 10%-20% difference was in the flexor absolute force and knee hip and ankle extensor explosive force. The level of muscular endurance of the lower extremities: the tolerance of the extensor group showed significant difference between left and right knee joints (P < 0.05). The differences were significant in the flexion and extensor groups between left and right ankle joints (P < 0.01). These results indicate that with the angular velocity increasing, the relative peak torque of bilateral hip and knee and ankle flexor and extensor was reduced in young male tennis players. The order of lower limb flexion and extension muscle peak torque was hip > knee > ankle. Moreover, the explosive force changes of ankle at rapid extension were obvious than those of hip and knee joint. There are significant differences in the heteronymous muscle strength ratio in the hip and ankle joint flexion and extension explosive force, so it is recommended to strengthen the flexor explosive force of the right hip joint. The hip flexion and extension endurance in young male tennis players is relatively good, and therefore, the endurance exercise of ankle extensor and knee flexor should be trained more.